Dietary Filamentous Fungi and Duration of Feeding Modulates Gut Microbial Composition in Rainbow Trout (Oncorhynchus mykiss) - Singh, Aprajita; Karimi, Sajjad; Vidakovic, Aleksandar; Dicksved, Johan; Langeland, Markus; Ferreira, Jorge A.; Taherzadeh, Mohammad J.; Kiessling, Anders; Lundh, Torbjörn (Frontiers in Marine Science, 2021)
Changes in gut microbial composition over time in rainbow trout fed differentially processed diets supplemented with the filamentous fungi Neurospora intermedia were investigated in a 30-day feeding trial. Fish were fed a reference diet, non-preconditioned diet (NPD), or preconditioned (heat-treated) diet (PD), with the same inclusion level of N. intermedia in diets NPD and PD. Gut microbiota were analyzed on day 0, 10, 20, and 30. Gut microbial composition was similar for all diets on day 0, but was significantly different at day 10 and day 20. On day 30, the gut again contained similar communities irrespective of diet. The overall gut microbiota for each diet changed over time. Abundance of Peptostreptococcus and Streptococcus was higher in the initial days of feeding in fish fed on commercial diet, while a significant increase in lactic acid bacteria (Lactococcus lactis) was observed on day 30. Feed processing (preconditioning) did not contribute largely in shaping the gut microbiome. These results indicate that dietary manipulation and duration of feeding should be considered when evaluating gut microbial composition in cultured fish. A minimum 30-day feeding trial is suggested for gut microbiome, host and diet interaction studies.